2004
DOI: 10.1161/01.hyp.0000128022.24598.4f
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Cyclic GMP Production via AT 2 and B 2 Receptors in the Pressure-Overloaded Aorta After Banding

Abstract: Abstract-Abdominal aortic banding induces upregulation of the angiotensin II (Ang II) type-2 (AT 2 ) receptor, thereby decreasing the contractile response to Ang II in the thoracic aorta of the rat. The aim of this study was to use a mouse model to clarify the mechanisms by which the banding elicits upregulation of the aortic AT 2 receptor and the subsequent attenuation of Ang II responsiveness. Concomitantly with the elevation in blood pressure and plasma renin concentration after banding, AT 2 -receptor mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 25 publications
3
42
0
Order By: Relevance
“…25,[27][28][29] Many previous studies have shown interaction between the B 2 and AT 2 receptors. [33][34][35][36][37][38] Siragy et al 35 showed that PD123319 suppressed basal bradykinin levels and prevented valsartan-induced increase in bradykinin levels in renal interstitial fluid. Our study is the first to examine this question in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…25,[27][28][29] Many previous studies have shown interaction between the B 2 and AT 2 receptors. [33][34][35][36][37][38] Siragy et al 35 showed that PD123319 suppressed basal bradykinin levels and prevented valsartan-induced increase in bradykinin levels in renal interstitial fluid. Our study is the first to examine this question in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ang II also induced apoptosis of VSMCs mediated by the AT-2 receptor in a mouse model of aortic banding-induced hypertension [57].…”
Section: Part II -Role Of the Renin-angiotensin-aldosterone System Onmentioning
confidence: 96%
“…The mechanism of AT 2 receptor-induced dilation in the pressure-overload model is BK-dependent, because the contractile response was restored with PD or icatibant in mice. 17 Ang II invoked a 9-fold increase in aortic cGMP that was abolished by either PD or icatibant. Functional vasodilator AT 2 receptors also have been demonstrated in the fetal aorta, where AT 2 receptor expression is extremely high.…”
Section: Vasodilation Mediated By Bk No and Cgmpmentioning
confidence: 96%